Current mode automatic gain control - Kasemsuwan, Varakorn; Arthansiri, Teerawat (My University, 2008)
This paper presents a current mode automatic gain control (AGC) using a new current mode pseudo exponential-control variable gain amplifier (VGA). The VGA is based on the 4th order Taylor's series approximation to obtain a large control range. The circuit Is designed using CMOS technology and can operate with ± 1 V supply voltages. The control range is 25 dB with the maximum error less than 0.5 dB. The power dissipation is 3 mW.
Keywords: AGC; Analog circuits; Current mode; Settling time